AN EMPIRICAL STUDY OF THE CONTENT COMPONENTS OF THE SELF-CONCEPT OF INDIVIDUALS WITH INCEST TRAUMA - Hlushchenko, Mykyta (Personality and environmental issues, 2025)
The article presents the analysis and interpretation of the results of an empirical study of the substantive components of the self-concept of individuals with incest trauma. In accordance with the stated goal of the study, the tasks of the work were: operationalization of the substantive components of the self-concept and interpretation of empirical indicators in the structure of the personality with incest trauma. To achieve the stated goals, a battery of psychodiagnostic methods was used: “Young schema Questionanire (YSQ-3)” (J. Yang), “Impact of Even Scale – Reviser (IES-R)” (D. Weiss, Ch. Marmar), “Scale of Incestuous Personality” (M. Dushkevych, M. Hlushchenko). The sample of the ascertaining experiment consisted of 173 individuals (of which 61 individuals who had experienced incest trauma and 112 individuals from the control group). The average age of the total sample was 32 years. Statistical processing of the results was carried out using the nonparametric Mann-Whitney U-test and one-way variance ANOVA analysis with subsequent interpretation of empirical components. The empirical study presented an idea of the phenomenology of the traumatic experience of incest in the structure of the self-concept of the individual. Based on the data obtained and comparative statistical procedures, it was analyzed that the manifestation of self-awareness of individuals with incest trauma unfolds around the constructive and destructive profile of the self-concept. It was established that the level of manifestation of indicators of the integrative nature of the traumatic event, the activation of dysfunctional cognitive schemes and the level of incestuousness is statistically higher among individuals with incest trauma in the group with a destructive rather than a constructive profile. It was found that the activation of the intrusion of traumatic memories complicates the mental state of the individual, forming a complex system of negative self-perception and emotional distress. The self-concept of individuals with incest trauma in a destructive profile is accompanied by the perception of their own defectiveness, excessive or insufficient sensitivity in the mental and physical spheres, a specific attitude towards sex, emotional derivation, and difficulties in interpersonal relationships. It is emphasized that understanding the self-concept allows for the identification of effective strategies for psychological support and psychosocial assistance at different (especially crisis) stages of ontogenesis in order to form a positive self-concept. The practical significance of the results lies in the possibility of their use by psychologists and psychotherapists to provide psychological support and assistance to individuals who have suffered incest trauma.